2018
DOI: 10.26603/ijspt20180058
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Lean During a Single-Leg Squat Is Associated With Trunk Lean During Pitching

Abstract: Background: Impaired trunk motion during pitching may be a risk factor for upper extremity injuries. Specifically, increased forces about the shoulder and elbow have been observed in pitchers with excessive contralateral trunk lean during pitching. Because of the difficulty in identifying abnormal trunk motions during a high-speed task such as pitching, a clinical screening test is needed to identify pitchers who have impaired trunk motion during pitching. Hypothesis/Purpose:The purpose of this study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Based on the fact that the SLS is a reliable assessment of LPHC strength and stability, sport performance, and lower extremity pain [9,11,14,[16][17][18], the purpose of this study to investigate the associations between bilateral SLS performance and reported pain in youth softball athletes. A positive correlation was found between bilateral differences of knee valgus at maximal knee flexion and pain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the fact that the SLS is a reliable assessment of LPHC strength and stability, sport performance, and lower extremity pain [9,11,14,[16][17][18], the purpose of this study to investigate the associations between bilateral SLS performance and reported pain in youth softball athletes. A positive correlation was found between bilateral differences of knee valgus at maximal knee flexion and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic data were collected at 100 Hz using an electromagnetic tracking system (trackSTAR TM , Ascension Technologies, Inc., Burlington, VT, USA) synced with The MotionMonitor (Innovative Sports Training, Chicago, IL, USA). Thirteen sensors were attached to the following landmarks: (1) posterior aspect of the torso at the first thoracic vertebrae (T1) spinous process; (2) posterior aspect of the pelvis at the first sacral vertebrae (S1); (3)(4) flat, broad portion of the acromion on the bilateral scapula; (5-6) lateral aspect of bilateral upper arm at the deltoid tuberosity; (7-8) posterior aspect of bilateral distal forearm, centered between the radial and ulnar styloid processes; (9-10) lateral aspect of bilateral upper leg, centered between the greater trochanter and the lateral condyle of the knee; (10-11) lateral aspect of bilateral lower leg, centered between the head of the fibula and lateral malleolus; (12) posterior aspect of the dominate hand below the second phalanx; and (13) superior aspect of the foot, midway between the metatarsophalangeal and talocalcaneonavicular joint [9,10,14]. A fourteenth, moveable sensor was attached to a plastic stylus and used for the digitization of bony landmarks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations